Tackling the readmission epidemic: a resident teaching service perspective - Ravi K. Sharma; Pradeep Dhakarwal; Janelle Violago; Robin Bhasin; Ibrahim Ghobrial (Greater Baltimore Medical Center, 2013)
Background: Readmission rates are projected to serve as quality measures that have the potential to negatively impact hospital and physician reimbursement. Individual physicians and hospitals are developing plans to reduce readmission rates. Successful plans should be based on specific data obtained from each individual type of practice. Objective: To analyze the etiological factors responsible for readmissions to various teaching services in a community hospital. This will serve to identify potentially correctable factors that will be the basis for developing practice-specific plans to reduce readmissions. Design: Retrospective detailed chart review. Setting: Community teaching hospital affiliated with a large academic health care system. Participants: Patients admitted to teaching services at a community hospital. Measurements: Data are presented as descriptive analysis. Results: Advanced chronic medical conditions (31%), patients’ lifestyle choices (28%), and new unrelated diagnoses (21%) are the major causes of readmissions. The remaining small percentage of readmissions is attributed to premature discharge, poor discharge planning, poor post-discharge follow-up, medication errors, and failure to implement medical care guidelines. Limitations: Retrospective study from a single center. Conclusions: Causes of readmission are diverse. Although most are universal, the relative contribution of each factor is unique to each population. Institutions should generate their own data in order to direct their resources toward ‘high return’ areas. Current studies emphasize the role of physicians and health systems in reducing readmission rates. However, the area of readmissions related to patients’ behaviors is not well explored. Our study identified the role of patients’ lifestyle choices as a major cause of readmission.